Efektifitas Penggunaan E-Learning Moodle, Google Classroom Dan Edmodo - Hakim, Abdul Barir (I-STATEMENT, 2016)
STIMIK ESQ use e-learning system to support teaching and learning process. But the e- learning system used is not utilized optimally, so that it can be concluded that the use of e-learning system has not generate interest and motivation of students and collaborative learning has not yet materialized. Therefore, comparison is done on most features in the e-learning system that has been used by STIMIK ESQ, namely Moodle, Edmodo and Google Classroom.